2004
DOI: 10.1111/j.1365-201x.2004.01331.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring type I angiotensin (AT1) receptor functions through gene targeting

Abstract: The renin-angiotensin system (RAS) modulates a diverse set of physiological processes including development, blood pressure, renal function and inflammation. The principal effector molecule of this system, angiotensin II, mediates most of these actions. The classically recognized functions of the RAS are triggered via the type 1 (AT(1)) class of angiotensin receptors. Pharmacological blockade of the AT(1) receptor lowers blood pressure and slows the progression of cardiovascular and renal diseases. Gene-target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 85 publications
2
46
0
Order By: Relevance
“…Kidney transplantation was carried out between genetically matched F 1 (C57BL͞6 ϫ 129) wild-type mice and F 1 (C57BL͞6 ϫ 129) mice homozygous for a targeted disruption of the Agtr1a gene locus encoding the AT 1A receptor (14). The AT 1A receptor is the major AT 1 receptor isoform in the mouse and the closest mouse homologue to the human AT 1 receptor gene (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kidney transplantation was carried out between genetically matched F 1 (C57BL͞6 ϫ 129) wild-type mice and F 1 (C57BL͞6 ϫ 129) mice homozygous for a targeted disruption of the Agtr1a gene locus encoding the AT 1A receptor (14). The AT 1A receptor is the major AT 1 receptor isoform in the mouse and the closest mouse homologue to the human AT 1 receptor gene (12).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of Ang II to increase blood pressure are mediated by AT 1 receptors (12), and these receptors are expressed in a variety of organ systems thought to play key roles in blood pressure homeostasis, including the heart, kidney, blood vessels, adrenal glands, and cardiovascular control centers in the brain (13). For example, in the vascular system, stimulation of AT 1 receptors causes potent vasoconstriction (14,15).…”
mentioning
confidence: 99%
“…The effects of Ang II occur via activation of two receptor subtypes, AT 1 and AT 2 (Hein, 1998;Crowley et al, 2004). The vasoconstrictor effects of Ang II are generally considered to result from activation of AT 1 receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The vasoconstrictor effects of Ang II are generally considered to result from activation of AT 1 receptors. In rodents, two AT 1 receptor subtypes (AT 1A and AT 1B ) exist, but cannot be distinguished using pharmacological inhibitors (Hein, 1998;Crowley et al, 2004). Thus, our third goal was to use genetically altered mice deficient in expression of AT 1A receptors to examine the importance of the AT 1A receptor in mediating the vascular effects of Ang II.…”
Section: Introductionmentioning
confidence: 99%
“…In rodents, BP and the pathophysiological effects of RAS are primarily mediated by the AT1a receptor. 1 The role of RAS in the pathogenesis of cardiovascular endorgan damages has been well characterized. Interestingly, clinical studies and animal experiments have demonstrated that inhibition of RAS with pharmacological agents such as angiotensin-converting enzyme inhibitors and AT1 receptor blockers (ARBs), as well as genetic disruption of RAS signaling components, diminishes end-organ damage, particularly atherosclerosis [2][3][4] and kidney injury.…”
mentioning
confidence: 99%